Digitalization of Islamic Education: Challenges to The Spirit of Humanistic and Transcendental Learning - Manasik, Jauhari; Kholis, Nur; Fatoni, Imam; Hasan, Sholikin (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This research aims to analyze the challenges of digitalization to the spirit of humanistic and transcendental learning in Islamic educational institutions. Using a descriptive qualitative approach with the type of literature study and field observation, this study collects data from various reputable scientific literature as well as information from Islamic education practitioners as key informants. The analysis was carried out through content analysis techniques to dissect the phenomenon of cyber interaction in the context of tarbiyah. The results of the study show that digitalization triggers the mechanization of learning which reduces the role of teachers from murabbi figures (soul guides) to mere technical facilitators. Screen-mediated interactions create a